Ղարաբաղի բարբառի առաջին ուսումնասիրությունները - Սարգսյան, Արմեն (ՀՀ ԳԱԱ ԼԻ հրատ.)
The Karabakh dialect boasts a history spanning many centuries; however, serious documentation and studies began only in the second half of the 19th century. The initial studies in this important domain of Artsakh's intangible cultural heritage were conducted by prominent linguists, folklorists, and educators of the time, including Kerovbe Patkanian, Ghazaros Aghayan, Galust Shermazanian, Makar Barkhudarian, Avetik Bahatrian, Manuk Abeghian, and Hrachia Acharian. Some of their recordings and studies were published as separate books, in various journals, and in collective volumes between the 1860s and 1890s, while others remain unpublished, stored in certain archives and museums. Although scientific transcription methods for dialects were not yet developed during that period, the authors endeavored to stay as faithful as possible to the dialect's pronunciation. All these studies serve as significant primary sources for the study of the Karabakh dialect and have played a crucial role in subsequent dialectological research. Карабахский диалект насчитывает многовековую историю, однако серьезная его документация и изучение начались лишь во второй половине XIX века. Первые исследования в этой важной области нематериального культурного наследия Арцаха проводили выдающиеся лингвисты, фольклористы и педагоги того времени, такие как Керовбе Патканян, Газарос Агаян, Галуст Шермазанян, Макар Баркударян, Аветик Бахатрян, Манук Абегян и Грачья Ачарян. Часть их записей и исследований была опубликована в виде отдельных книг, в различных журналах и коллективных сборниках в период с 1860-х по 1890-е годы, а другие остаются неопубликованными, хранясь в архивах и музеях. Несмотря на то, что в тот период еще не были разработаны научные методы транскрипции диалектов, авторы стремились максимально точно передать произношение диалекта. Все эти исследования являются значимыми первоисточниками для изучения карабахского диалекта и сыграли важную роль в дальнейшем диалектологическом исследовании.
Keywords: Բարբառագիտություն